Brewers' rice, a by-product from rice processing, has antiproliferative activity on human colorectal cancer (HT-29) cell line - Tan, B. L.; Mohd Esa, Norhaizan; Hamzah, Hazilawati; Karim, Roselina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Colon carcinogenesis is a malignant tumor, and is well-known as the third leading cancer, which contributes to high mortality and morbidity worldwide. Brewers' rice, known locally as temukut, consists of a mixture of broken kernels with rice bran and rice germ which is a byproduct produced in the rice industry. Although extensive studies on the anti-cancer properties of rice bran, published data on the cytotoxicity of brewers' rice are very limited. The present study was conducted to evaluate the apoptosis induction capability of the water extract of brewers' rice (WBR) on human colorectal cancer (HT-29) cell line. The HT-29 cells were treated with various concentrations (16, 32, and 64 μg/mL) of WBR for 24 and 48 hours. The morphological analysis of apoptotic cells was evaluated using inverted light microscope and fluorescence microscope. The apoptotic HT-29 cells was evaluated using Annexin V-FITC and propidium iodide (PI) staining apoptosis test and cell cycle analyses. The data obtained were evaluated using a one-way analysis of variance (ANOVA) and P < 0.05 was considered statistical significant. Overall analyses indicated that WBR induced typical characteristics of apoptosis in HT-29 cells, including nuclear fragmentation (NF), nuclear compaction (NC), apoptotic bodies (AB), cellular shrinkage (CS), and chromatin condensation (CC), as visualized under inverted light microscope and fluorescence microscope. Cell cycle analyses and Annexin V-FITC and propidium iodide (PI) staining apoptosis test using flow cytometry revealed that WBR induced apoptotic population in HT-29 cells. In this study, our findings provide clear evidence that WBR inhibits the growth of HT-29 cells via induction of apoptosis. Taken together, we suggest that WBR may be a potential candidate for the prevention and treatment of colorectal cancer.